2019
DOI: 10.1016/j.ajhg.2018.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Mutations in ARMC2 Lead to Severe Astheno-Teratozoospermia Due to Sperm Flagellum Malformations in Humans and Mice

Abstract: Male infertility is a major health concern. Among its different causes, multiple morphological abnormalities of the flagella (MMAF) induces asthenozoospermia and is one of the most severe forms of qualitative sperm defects. Sperm of affected men display short, coiled, absent, and/or irregular flagella. To date, six genes (DNAH1, CFAP43, CFAP44, CFAP69, FSIP2, and WDR66) have been found to be recurrently associated with MMAF, but more than half of the cases analyzed remain unresolved, suggesting that many yet-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
119
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 36 publications
2
119
1
1
Order By: Relevance
“…MMAF is an autosomal‐recessive disorder linked to mutations in several genes, including DNAH1 (Ben Khelifa et al., ; Wang et al., ), DNAH2 (Li et al., ), CFAP43 , and CFAP44 (Sha et al., ; Tang et al., ; Wu et al., ), CFAP69 (Dong et al., ; He et al., ), CFAP251 (also known as WDR66 ) (Kherraf et al., ; Li et al., ), FSIP2 (Martinez et al., ), ARMC2 (Coutton et al., ), AK7 ( Lores et al., ), QRICH2 (Shen et al., ), SPEF2 (Liu et al., ; Sha et al., ), TTC21A (Liu et al., ), and CEP135 (Sha et al., ). However, further research is needed to determine the genetic causes of the remaining 40%–50% of the MMAF patients (Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…MMAF is an autosomal‐recessive disorder linked to mutations in several genes, including DNAH1 (Ben Khelifa et al., ; Wang et al., ), DNAH2 (Li et al., ), CFAP43 , and CFAP44 (Sha et al., ; Tang et al., ; Wu et al., ), CFAP69 (Dong et al., ; He et al., ), CFAP251 (also known as WDR66 ) (Kherraf et al., ; Li et al., ), FSIP2 (Martinez et al., ), ARMC2 (Coutton et al., ), AK7 ( Lores et al., ), QRICH2 (Shen et al., ), SPEF2 (Liu et al., ; Sha et al., ), TTC21A (Liu et al., ), and CEP135 (Sha et al., ). However, further research is needed to determine the genetic causes of the remaining 40%–50% of the MMAF patients (Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic characterization of this phenotype began in 2014 with the identification of DNAH1 (dynein axonemal heavy chain 1) as a major gene implicated in MMAF . After the development and the introduction of high throughput sequencing (HTS) techniques such as whole exome sequencing (WES), deleterious mutations were formally identified in eight additional MMAF genes ( AK7 , ARMC2 , CFAP43 , CFAP44 , CFAP69 , FSIP2 , TTC21A , and WDR66 ) showing the high genetic heterogeneity of this phenotype. Despite these important advances in gene identification, about half of the MMAF cases remain idiopathic without a genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that the MMAF phenotype is associated with genetic mutations. Previous studies revealed that mutations in DNAH1 (MIM: 603332), DNAH2 (MIM: 603333), AKAP4 (MIM: 300185), CCDC39 (MIM: 613798), AK7 (MIM: 615364), CFAP251 (MIM: 618146), CEP135 (MIM: 611423), FSIP2 (MIM: 615796), ARMC2 (MIM: 611226), QRICH2 (MIM: 618304), SPEF2 (MIM: 610172), CFAP69 (MIM: 617949), CFAP43 (MIM: 617558) and CFAP44 (MIM:617559) could cause the human MMAF phenotype . However, more research is needed to reveal the etiology of the remaining 30%–40% of MMAF cases.…”
Section: Introductionmentioning
confidence: 99%